PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION PADA PT VICTOR DUA TIGA MEGA KABUPATEN BARITO UTARA - Rae Shita (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2025)
This study aims to analyze the influence of workload and work environment on employee turnover intention at PT. Victor Dua Tiga Mega in Barito Utara Regency. The high level of turnover intention in this company has become a major concern, as it affects the quality and performance of the organization. The research method used is quantitative with a correlational approach, where data is collected through a questionnaire distributed to 33 employees. The analysis results indicate that both workload and work environment have a significant impact, both simultaneously and partially, on turnover intention. Additionally, workload has proven to be the dominant factor influencing employees' intention to leave the organization. These findings are expected to provide insights for management in efforts to improve job satisfaction and reduce employee turnover intention, allowing the company to retain quality human resources.